On different types of dignity in nursing care: a critique of Nordenfelt - Wainwright, Paul; Gallagher, Ann (2008)
Dignity appears to be an important concept in nursing philosophy and more widely in health care policy and provision. Recent events in the UK have generated much interest in the subject. However, there appears to be some confusion about the precise meaning and application of the concept. An influential contribution to the debate has come from Nordenfelt, who, as part of a European project investigating dignity and the care of older people, has proposed a four-part typology of dignity. In this article, we will explore some of the background to the dignity debate in UK nursing and health care, give a brief overview of Nordenfelt's position, offer some criticisms of his work and propose some modifications to his view.
Keywords: Nordenfelt; Dignity; Ethics; Nursing